Between the Human and the Dancer: Practice, Academia,and Ethics in Contemporary Ecuadorian Architecture - Alicea Matos, Mónica (Artes: Architecture, Technology and Sustainability, 2026)
Between thinking and doing, a fissure opens—one that cuts across contemporary architectural practice. This essay is grounded in the author’s critical reflection on her experience in both academia and professional practice. From this situated standpoint, the text offers a broad survey of Ecuador’s contemporary challenges, addressing the dynamics of the real estate market, institutional fragility, academic training, and professional responsibility. It is argued that the growing divide between academia and professional practice, together with the difficulty of questioning the systems within which we operate, has contributed to the polarization of the profession between market-driven logics and forms of resistance with limited influence on the material transformation of the city. In this context, urban development is driven more by economic profitability than by environmental, social, or urban considerations, while architecture frequently privileges aesthetic trends over technical standards for environmental and human protection. Adopting an approach akin to gonzo journalism, the author positions herself as an active participant in what she analyzes. In the text, she relinquishes the illusion of apolitical neutrality and argues that only through self-critique is it possible to construct a truly conscious critique and open pathways for transformation in architectural practice.